Pemecahan Masalah Kolaboratif dalam Pengantar Fisika Berkelanjutan dengan Rencana Pembelajaran Semester Kursus Proyek Cerdas Lahan Gambut - Santiani, Santiani; Annovasho, Jhelang; Winarto, Winarto (Jurnal Penelitian Pendidikan IPA, 2023)
Education is one of the factors that prepare societies to handle climate change. Humanity must step up efforts to reduce greenhouse emissions and prepare humanity for future crises. The development and validation the SLP of the SIP-SPP course is an effort to mitigate climate change through physics learning. The Plomp development design with three main stages: preliminary research, prototyping, and assessment to produces valid, practical, and effective semester learning plan products. The characteristics of the resulting semester learning plan product are the learning objective of adopting the thirteenth SDGs is climate change mitigation, adopting EfSD competencies are CPS, assessment learning objectives with environmental literacy questionnaires and CPS performance observation rubrics in groups, learning activities based on peatland-smart projects, learning content heat and thermodynamics, peatlands, climate change, and region. SLP is valid and reliable according to experts and practitioners, practical and easy to use, and can improve the CPS of prospective physics teacher students. SLP of SIP-SPP needs to be developed and validated to make it easier for lecturers and science lecturers, especially physics, to adopt SDGs and EfSD in learning. Environmental literacy of prospective teacher students will be a mitigation of climate change.